Reserved for murder - Gilbert, Victoria (A Booklover's B&B mystery, 2021)
When the president of a reclusive writer's fan club is found dead after a book signing, Charlotte Reed, the owner of Chapters B&B, her neighbor Ellen and Ellen's trusty Yorkshire terrier must page through the clues to catch a killer before the author meets the same fate.